Regime jurídico das reorganizações: a necessária distinção das reorganizações societárias, empresariais e associativas para proteção jurídica do investimento privado - Castro, Rodrigo Rocha Monteiro de (2015)
This thesis provides a new approach to reorganizations by initially identifying reorganization as a category in which the following reorganizations are inserted (i) corporate; (ii) business; and (iii) associative. This distinction leads to the necessary comprehension that the legal framework applicable to each type of reorganization is different and that the person carrying the reorganization may choose from one of these types of reorganization to fulfil its own interests or to have personal gains without sharing them with the other shareholders (when such person is a controlling shareholder) or with any shareholder (when such person is a managerial controller). This scenario is stressed when the capital structure of companies change and mainly in public listed companies subject to minority corporate control or managerial business control. There are incentives for choosing one of these reorganizations types to prevent certain persons (all the shareholders or only the minority shareholders, as the case may be) from participating in the decision making process (corporate approval of the reorganization), from exercising rights that they are entitled when other types of reorganizations are chosen (such as a mandatory offer of acquisition of shares or right of withdrawal) and from benefiting the same conditions applicable to the person that chooses the type of the reorganization. Therefore, based in the different legal frameworks of reorganizations and conflicts that may exist between controlling/minority shareholders and partner/managerial controller, it is necessary to create mechanisms to protect the private investment